2014
DOI: 10.1165/rcmb.2013-0303oc
|View full text |Cite
|
Sign up to set email alerts
|

IκBβ-Mediated NF-κB Activation Confers Protection against Hyperoxic Lung Injury

Abstract: Supplemental oxygen is frequently used in an attempt to improve oxygen delivery; however, prolonged exposure results in damage to the pulmonary endothelium and epithelium. Although NF-kB has been identified as a redox-responsive transcription factor, whether NF-kB activation exacerbates or attenuates hyperoxic lung injury is unclear. We determined that sustained NF-kB activity mediated by IkBb attenuates lung injury and prevents mortality in adult mice exposed to greater than 95% O 2 . Adult wild-type mice dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
(68 reference statements)
2
10
0
Order By: Relevance
“…Furthermore, previous studies have shown that inflammatory stress-induced NF-B activation disrupts lung branching and lung morphogenesis (5, 10). In contrast, multiple studies have demonstrated that NF-B activity is protective against oxidative stress, demonstrated by increased injury with NF-B inhibition ( tivation have improved survival attributable to enhanced expression of NF-B regulated antiapoptotic genes (44). Of note, neonatal AKBI mice exposed to hyperoxia demonstrate early and enhanced expression of proinflammatory NF-B-regulated target genes compared with similarly exposed WT mice and previous reports (4,15,19,37,56,57).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, previous studies have shown that inflammatory stress-induced NF-B activation disrupts lung branching and lung morphogenesis (5, 10). In contrast, multiple studies have demonstrated that NF-B activity is protective against oxidative stress, demonstrated by increased injury with NF-B inhibition ( tivation have improved survival attributable to enhanced expression of NF-B regulated antiapoptotic genes (44). Of note, neonatal AKBI mice exposed to hyperoxia demonstrate early and enhanced expression of proinflammatory NF-B-regulated target genes compared with similarly exposed WT mice and previous reports (4,15,19,37,56,57).…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, IB␤ has no nuclear export sequence and, once in the nucleus, acts to stabilize NF-B DNA binding and potentiate NF-B activity and downstream gene expression (47). This sustained NF-B activity protects cells from oxidant stress-induced cell death and prevents pulmonary oxygen toxicity in adult mice (44,58).…”
mentioning
confidence: 99%
“…p65 is then released and free to associate with the p50 subunit; releasing the active NF-κB to enter the nucleus and activate gene expression [26]. Sustained activation of NF-κB has been shown to attenuate hyperoxia-induced mortality in adults and improve survival, preserve lung development and decrease hyperoxic lung injury in neonatal mice [27]. In human pulmonary epithelial cells, NF-κB pathway activation decreased hyperoxia induced cell death [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have previously reported that AKBI mice are resistant to oxidative stress and hyperoxic lung injury. (35, 43, 44) Given the potential interaction between oxidative stress and NFκB signaling, we assessed the expression of the two major anti-oxidant NFκB target genes, manganese superoxide dismutase (MnSOD) and ferritin heavy chain, and two major pro-oxidant NFκB target genes, xanthine oxidase/dehydrogenase (XOR) and cyclooxygenase-2 (COX-2). (45) Importantly, expression of these NFκB targets was not different between endotoxemic WT and AKBI mice (Supplemental Figure 2).…”
Section: Resultsmentioning
confidence: 99%